PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP GERAKAN SALAT SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 7 SUNGAI RAYA TAHUN AJARAN 2025-2026 - Sella Safutri; Wahdah; Rini Elvri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students’ prayer movement skills in Islamic Religious Education (PAI) at SMP Negeri 7 Sungai Raya. One effort to improve these skills is through the implementation of an effective learning model. Therefore, the researcher was interested in applying the Picture and Picture learning model to determine its effect on the prayer movement skills of seventh-grade students. This study employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The population consisted of all seventh-grade students at SMP Negeri 7 Sungai Raya. The sample comprised 64 students, including 32 students in the experimental class and 32 students in the control class. Data were collected through observation of students’ prayer movement practices and analyzed using descriptive and inferential statistics. The results showed that the average pre-test score of the experimental class was 52.81, which increased to 90.91 in the post-test. Meanwhile, the average pre-test score of the control class was 51.88, increasing to 63.38 in the post-test. The results of hypothesis testing indicated a significant effect of the Picture and Picture learning model on students’ prayer movement skills. Therefore, the Picture and Picture learning model proved to be effective in improving students’ prayer movement skills in Islamic Religious Education at SMP Negeri 7 Sungai Raya.